2012
DOI: 10.1088/0004-6256/143/3/75
|View full text |Cite
|
Sign up to set email alerts
|

An Old Supernova Remnant Within an H Ii Complex at ℓ ≈ 173°: FVW 172.8+1.5

Abstract: We present the results of H i 21 cm line observations to explore the nature of the high-velocity (HV) H i gas at ∼ 173• . In low-resolution H i surveys this HV gas appears as faint, wing-like, H i emission that extends to velocities beyond those allowed by Galactic rotation. We designate this feature as Forbidden Velocity Wing (FVW) 172.8+1.5. Our high-resolution (3. 4) Arecibo H i observations show that FVW 172.8+1.5 is composed of knots, filaments, and ring-like structures distributed over an area of a few d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 50 publications
7
47
0
Order By: Relevance
“…Triggered Star Formation. Kang et al (2012) found evidence that the entire Sh2-235 complex has been affected by a supernova remnant (SNR) with an age of ∼0.3 Myr, based on their observations of the H I 21 cm line. Their inferred age, however, is too short for the SNR to have triggered the formation of the ionizing stars in the most extended, oldest of the visible H II regions, namely .…”
Section: Discussionmentioning
confidence: 99%
“…Triggered Star Formation. Kang et al (2012) found evidence that the entire Sh2-235 complex has been affected by a supernova remnant (SNR) with an age of ∼0.3 Myr, based on their observations of the H I 21 cm line. Their inferred age, however, is too short for the SNR to have triggered the formation of the ionizing stars in the most extended, oldest of the visible H II regions, namely .…”
Section: Discussionmentioning
confidence: 99%
“…In addition it is reported that there are about 14 embedded SFRs having ages ∼3-5 Myrs (cf. Kang et al 2012, and references therein). It has also been proposed that the formation of these young objects could have been triggered by a older generation of stars (Kang et al 2012, and references therein).…”
Section: Physical Conditions In the Auriga Regionmentioning
confidence: 99%
“…region: a series of triggered star formation Kang et al (2012) estimated that the shell is expanding with a velocity of ∼55 km s −1 and the kinetic energy of the shell is ∼ 2.5 × 10 50 ergs. They also detected hard X-ray emitting hot gas inside the shell with a thermal energy of ∼ 3 × 10 50 ergs.…”
Section: Star Formation History In the Auriga Bubblementioning
confidence: 99%
See 1 more Smart Citation
“…When the velocity dispersion is considered, the observed Hi profile would have a shape of a flat profile convolved with a Gaussian profile along the velocities (e.g., Park et al 2013;Kang et al 2012). The Hi mass follows the same shape of the Hi profile along the velocities.…”
Section: Hi Mass Extrapolationmentioning
confidence: 99%